Analisis Faktor Produksi Kalapa Sawit Rakyat Menurut Tipologi Lahan di Kabupaten Indragiri Hilir Provinsi Riau - Heriyanto Heriyanto; Asrol Asrol; Detri Karya; Verry Yarda Ningsih (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Heriyanto et al, 2018. Analysis of the Production Factors of the People's Palm Oil According to the Land Typology in Indragiri Hilir Regency, Riau Province. JLSO 7(1):14-25.Â Palm oil commodities are one of the plantation sub-sector commodities that increase the income of farmers and the community, provide processing industry raw materials that create added value. The land cultivated by independent oil palm farmers consists of land land, tidal peatlands, coastal peatlands and coastal land. The difference in typology of this land will contribute to different production. The research aimed to analyze the oil palm production and the dominant factor affecting oil palm production according to the typology of land in Indragiri Hilir Riau Province. The data were analyzed using descriptive statistics and built multiple regression models with the dummy variable method of Ordinary Least Square (OLS). The results of the study showed that the production of oil palm cultivation on land is the highest compared to the typology of tidal peatland, coastal peat and coastal land. The dominant factors affecting palm oil production in Indragiri Hilir Regency were the amount of fertilizer use, labor, age of plants, herbicides and dummy typology of land. In order to obtain optimal production, this study recommended doing oil palm farming in accordance with the correct cultivation techniques in accordance with the characteristics of land typology. Besides that the use of balanced fertilizer (elements of N, P, and K) in accordance with the recommended needed to be applied.